2021
DOI: 10.1038/s41598-020-77918-x
|View full text |Cite
|
Sign up to set email alerts
|

Visual behavior modelling for robotic theory of mind

Abstract: Behavior modeling is an essential cognitive ability that underlies many aspects of human and animal social behavior (Watson in Psychol Rev 20:158, 1913), and an ability we would like to endow robots. Most studies of machine behavior modelling, however, rely on symbolic or selected parametric sensory inputs and built-in knowledge relevant to a given task. Here, we propose that an observer can model the behavior of an actor through visual processing alone, without any prior symbolic information and assumptions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…How to assess this is an open research question. One option is to follow what is done with humans where, for example, AToM is indirectly inferred by inducing actions that reveal the ASI observer's understanding of the state of mind of an agent (Chen et al, 2021b ). Another option is to develop agent assessments based upon ToM tests used to evaluate social intelligence in humans.…”
Section: Socially Intelligent Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…How to assess this is an open research question. One option is to follow what is done with humans where, for example, AToM is indirectly inferred by inducing actions that reveal the ASI observer's understanding of the state of mind of an agent (Chen et al, 2021b ). Another option is to develop agent assessments based upon ToM tests used to evaluate social intelligence in humans.…”
Section: Socially Intelligent Agentsmentioning
confidence: 99%
“…This is generally seen as the ability to recognize and attribute mental states, beliefs, desires, and intentions to others. As a core process in social cognition, it is fundamental to our ability to interact (Chen et al, 2021b ). Said another way, social intelligence can be considered the manifestation of Theory of Mind in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, these sensory systems could be mapped onto the sensing agent and then applied to probabilistic models of observed agents, thus mimicking the reality of shared experience. Recently, Chen et al reported such a system using a visual behavior robotic model that was able to visualize the future plans of another machine with 98.5% success across four different activities (Chen et al, 2021). If similar strides are made in other robotic sensory paradigms, it is reasonable to imagine an integrative AI system possessing multiple sensory modalities as well as a capacity for mapping these sensory experiences onto observed agents.…”
Section: A Neuroscientific Approach To the Alignment Problemmentioning
confidence: 99%
“…Deep learning methods, and in particular convolutional neural networks (CNNs), have been successfully used in a wide range of design applications, from generating car silhouettes to predicting molecule structures [6][7][8][9]. Furthermore, CNNs have the capacity to model complex phenomena, such as classifying objects in images, recognizing actions in videos and predicting the dynamic behaviour of a lava lamp or a candle flame, as well as to predict the behaviour of another agent in a game of hide and seek [10][11][12]. However, in most cases, CNN models are trained on raw image data, without access to user-selected relevant variables or analytical models.…”
Section: Deep Neural Network Models For Visual Intuitionmentioning
confidence: 99%